INTEGRATED LEARNING IN DRAMA COURSE USING YOUTUBE - Christiana Evy Tri Widyahening; Ulupi Sitoresmi (RESEARCH FAIR UNISRI, 2021)
The purpose of this study was to explain and describe the application of integrated learning in digital-based Drama learning to 6th semester students at Slamet Riyadi University, Surakarta. This research is a qualitative descriptive study with a single case study type which only examines one research subject. The research subjects were students in semester VI in the English Education Study Program, Unisri Surakarta. This study uses the steps proposed by Miles and Huberman. The research location is in semester VI of the English Language Education Study Program, FKIP, Slamet Riyadi University Surakarta and in the central library of the Slamet Riyadi University Surakarta. The results showed that the application of integrated learning in digital-based drama learning was very good and interesting. This is also supported by four student language skills that are increasing, namely writing, reading speaking and listening. In addition, students are also increasingly able to cultivate creative power, cooperation between friends, foster sympathy and empathy, and self-confidence through drama scripts that they write themselves. They then played their work in front of the camera screen and uploaded it through YouTube social media so that the wider community could watch their role play. This is a challenge in itself for students and it makes them even more trying to give their best from the first stage, namely the process of writing drama scripts, practicing playing dramas, playing roles, and in the final stage they upload the results of playing these roles to YouTube social media. The effectiveness of integrated learning is reflected in the meaning of learning. Meaningful learning produces students who are active in a fun teaching and learning process, resulting in two-way communication between lecturers and students. Fun learning will run well if the lecturer has high creativity and has variations in the teaching and learning process so that the end result is that students can get good and meaningful learning achievements. Keywords: Integrated Learning, Drama Learning, Qualitative Descriptive, Case Study, YouTube